Tuition and Fee Waivers, Residency Exemptions, Reduced Fee Courses - Washington State Higher Education Coordinating Board, Olympia; Washington State Higher Education Coordinating Board, Olympia ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
This report of the Washington State Higher Education Coordinating Board provides a review of tuition and fee waiver programs submitted by each state university, regional university, state college, and the community college system; and presents recommendations for the continuation, modification, or termination of these programs. The review describes the scope of the various existing programs, discusses what the cost of these programs are to the state and its higher education institutions, examines the growth of these programs over the years, and reviews what the objectives are in evaluating them. Additionally, various program evaluation alternatives that were given to the Board for its consideration are explained. Appendices, comprising half the report, provide: (1) a list of programs by common purpose or goal and identified by mandatory/permissive authority, (2) a listing of the mandatory and permissive programs and amounts of operating fee revenue waived for 1992-93, and (3) the evaluation procedure and criteria used for program reviews. (GLR)
ERIC Note: For related documents, see HE 027 027-033.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Comparative Analysis; Educational Legislation; Fees; Financial Support; Graduate Study; Higher Education; In State Students; Operating Expenses; Place of Residence; Program Evaluation; Public Colleges; State Universities; Student Financial Aid; Tuition; Undergraduate Study; Tuition Waivers -- Washington; Reports, Descriptive